Analytic Study in the “Sufi Comic Book 3” About the Concept of Self Purification in Islamic Education - Iftitahul Aini; Hariyanto Hariyanto (Educan : Jurnal Pendidikan Islam, 2020)
The objectives of this study are 1) Knowing the Tazkiyah An-Nafs concept in Islamic education, 2) Knowing the Tazkiyah An-Nafs concept in "Sufi Comic Book 3", and 3) Analyzing the strengths and weaknesses of the Tazkiyah An-Nafs concept in " Sufi Comic Book 3 ". This type of research is library research, so in collecting data the researcher uses primary data, namely the book "Book of Sufi Comics 3" by Bayu Priambodo. Whereas secondary data was obtained from journals and other literature relating to the discussion of this title. The data obtained is by using the documentary method. Whereas in the analysis the researcher used the content analysis method, namely by looking at the content of the communication content qualitatively, on how the researcher interpreted the contents of communication, read symbols, and interpreted the contents of symbolic interactions that occur in communication. So from this simple study, the researcher concludes that: 1) The concept of Tazkiyah An-Nafs in Islamic education includes four realms, namely purifying the body, purifying morals, purifying the heart, and purifying the deepest soul so as not to be bound by worldly lust. 2) In "Sufi Comic Book 3" consists of means of realizing Tazkiyah An-Nafs and its realization which includes sincerity, tawakal, gratitude, zuhud, honest, patient, khauf and raja', amar ma'ruf nahi munkar, and prayer. 3) Analysis of the advantages in writing, Sufi Comic Book 3 contains clarity and conciseness that does not confuse the reader, and the drawback is that this comic publication has not yet entered the digital market and is still read in printed book form. This is certainly slightly contrary to the tendency of millennial generation as a marketing target that prefers electronic books to printed books.